Employee performance reviewed from motivation, discipline, leadership and environment (study at Surakarta city health office) - Subagiyo, Didik; Istiatin, Istiatin; Titisari, Kartika Hendra (Enrichment : Journal of Management, 2024)
This research aims to determine the influence of motivation, discipline, leadership and environment on employee performance at the Surakarta City Health Service. This research method uses a quantitative descriptive approach. The population in the study was 80 employees of the Surakarta City Health Service, all of whom were taken as research samples using total sampling techniques. Data collection using questionnaires. The data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and coefficient of determination. The research results show that partially motivation, discipline, leadership and environment have a positive and significant effect on employee performance at the Surakarta City Health Service. Therefore, suggestions for the management of the Ssurakarta City Health Service need to continue to improve motivation, discipline, leadership and the environment so that they can achieve maximum performance